Compressive performance of bamboo sheet twining tube-confined recycled aggregate concrete columns. (14th March 2022) - Nie, Yuhan; Wei, Yang; Zhao, Kang; Ding, Mingmin; Huang, Linjie
Highlights: A new bamboo sheet twining tube-confined recycled aggregate concrete (BSTRAC) column was proposed. Effect of the BCT thickness and the volume content of short bamboo strips on RAC were investigated. The strength of BSTRACs was predicted and compared with experimental results. The axial stress–strain curve of the BSTRACs under compression was simulated. Abstract: This paper proposes a new structure for a recycled aggregate concrete (RAC) column confined by a bamboo composite tube (BCT), and the performance of the RAC is further improved by mixing short bamboo strips. An experimental and analytical study of the behavior of bamboo sheet twining tube-confined recycled aggregate concrete (BSTRAC) columns under axial compression is presented. A total of thirty-six axially loaded BSTRAC columns were manufactured to investigate the effects of the number of bamboo sheet layers (BCT thickness) and the volume content of short bamboo strips. The results indicated that the BCT had strong lateral confinement as well as the ability to bear axial loads, which resisted lateral expansion deformation, and the increase in BCT thickness led to an increase in compressive strength and ductility. In addition, the short bamboo strips could improve the compressive strength, ductility and residual bearing capacity of the axially loaded BSTRAC column. Based on the compressive performance of short bamboo strip-reinforced RAC, ten existing FRP-confined concrete models were considered to predict the ultimate stress, ultimate strain and axial stress–strain curves of BSTRAC columns. It can be concluded that some existing models can be used to predict the ultimate stress and ultimate strain of BSTRAC columns accurately; moreover, a few models provide reasonable predictions for the BSTRAC specimens of stress–strain curves.